THE ROLE OF THE CONCEPT OF "LIFE" IN THE DEVELOPMENT OF LANGUAGE AND CULTURE - Mashkhura Safarova Dilmurodovna (Journal Park Publishing, 2025)
This study explores the linguistic and cultural dimensions of the concept of "life" through a comparative analysis of its lexical realizations in English (life), Russian (zhizn'), and Uzbek (hayot). Using the theoretical framework of linguistic relativity, the study looks at etymological roots, semantic domains, and culturally ingrained phrases to show how language shapes ideas of life, free will, and social harmony. The findings show both culturally particular emphases (individualism in English, endurance and fatalism in Russian, and spiritual-communal harmony in Uzbek) and universal biological foundations. These variances corroborate the Sapir-Whorf hypothesis by confirming the reciprocal effects of language and culture. The results highlight the function of language in cognitive framing and cultural transmission, with ramifications for multilingual policy, education, and cross-cultural communication.
Keywords: Life concept, linguistic relativity, comparative linguistics, cultural semantics, English, Russian, Uzbek, language and culture.